Indexing the Diffraction Patterns and Investigating the Crystal Structure of Pb-doped Strontium Ferrites - Ullah, Z.; Atiq, S.; Naseem, S. (Journal of Scientific Research, 2013)
Strontium hexaferrites were prepared in powder form by sol-gel auto-ignition technique and Pb was doped in different concentrations to attain the various compositions Sr1-xPbxFe12O19 (x = 0.00, 0.05, 0.10, 0.15, 0.20). Sintering treatment of the samples was made at 800 oC for the development of stable hexagonal phase. X-ray diffraction analysis of the samples was carried out for the confirmation and determination of crystal structure of the material. Data obtained from X-ray diffraction analysis helped in determining various parameters of the samples like lattice parameters, volume of the unit cell, crystallite size, bulk density of the samples, X-ray density and porosity of the samples. Keywords:Ferrites; Sol-gel method; X-Ray diffraction; Crystal structure. © 2013 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi: http://dx.doi.org/10.3329/jsr.v5i2.11578 J. Sci. Res. 5 (2), 235-244 (2013)